Developpement d'un systeme d'aide a la gestion des canaux d'irrigation. In FrenchDeveloping a system to help manage irrigation canals - Rozenknop, A.; Loisel, C. (International Irrigation Management Institute, 1996)
The aim of this 3 months training course was to re-program and develop an irrigation management information system created in 1992 for local use in Sri Lanka. The main points of the new version are: ability to manage and to have hydraulic simulations via SIC on a network of branched canals; much more user friendly; direct application is possible in several parts of Pakistan, facilities for installation and opportunities to adapt. After a short description of the background, this report studies the global interest of computerizing an information system for irrigation canal management. Part 3 explains in the main what data are required and how they are stored in tables. Part 4 advises a list of further improvements.